Modern means of assessing the impact of emergencies on the environmental condition of the ground layer of atmosphere - Turevych, Anastasiia; Madzhd, Svitlana; Cherniak, Larysa; Pavlyuk, Anatoliy; Ojeh, Vincent (My University, 2021)
The problem of emergencies will not leave humanity as long as it exists, and therefore it is necessary to at least create conditions under which it is possible to reduce the risks of injuries, diseases and deaths of people who are in the emergency zone. This can be achieved by raising awareness of the nature of the emergency, the hazardous substances that are released in connection with it. Theoretical analysis of various remote means of assessing the impact of emergencies of man-made areas on the ecological state of the atmospheric air of the surrounding areas. It has been found that the use of remote sensing equipment greatly simplifies the procedure of operational monitoring of the environment during emergencies, as well as contributes to the health of professionals. A comparison of different remote means of environmental monitoring of air quality was performed: In particular, stationary automatic stations, mobile automatic stations, probes, and unmanned aerial vehicles (UAVs) were compared. It is proposed to use UAVs as remote means of operational monitoring of air quality. The functional scheme of UAV system implementation for the needs of operative ecological monitoring is offered. The legal features of the use of unmanned aerial vehicles as remote means of monitoring air quality during emergencies are analyzed

Проблема надзвичайних ситуацій не покине людство, поки вона існує, а тому необхідно принаймні створити умови, за яких можна знизити ризики травмування, захворювань і загибелі людей, які перебувають у зоні надзвичайної ситуації. Цього можна досягти шляхом підвищення обізнаності про природу надзвичайної ситуації, небезпечні речовини, які викидаються у зв’язку з нею. Теоретичний аналіз різноманітних дистанційних засобів оцінки впливу надзвичайних ситуацій техногенних територій на екологічний стан атмосферного повітря прилеглих територій. Встановлено, що застосування засобів дистанційного зондування значно спрощує процедуру оперативного моніторингу навколишнього середовища під час надзвичайних ситуацій, а також сприяє збереженню здоров’я фахівців. Проведено порівняння різних дистанційних засобів екологічного моніторингу якості атмосферного повітря: зокрема порівнювали стаціонарні автоматичні станції, мобільні автоматичні станції, зонди та безпілотні літальні апарати (БПЛА). Пропонується використовувати БПЛА як дистанційний засіб оперативного моніторингу якості повітря. Запропоновано функціональну схему реалізації системи БПЛА для потреб оперативного екологічного моніторингу. Проаналізовано правові особливості використання безпілотних літальних апаратів як дистанційного засобу моніторингу якості атмосферного повітря під час надзвичайних ситуацій
Keywords: modern means; assessing the impact; emergencies; сучасні засоби; оцінка впливу; надзвичайні ситуації; кафедра екології та екоменеджменту